2021
DOI: 10.1136/jim-2020-001588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rosiglitazone on Circulating Malondialdehyde (Mda) Level in Diabetes Based on a Systematic Review and Meta-Analysis of Eight Clinical Trials

Abstract: Patients with type 2 diabetes have high levels of malondialdehyde (MDA), and clinical data suggest a reducing effect of rosiglitazone (RSG) on the level of MDA in these patients. However, the results of available studies on the level of MDA in RSG-treated patients are not univocal. This meta-analysis aimed to assess the impact of RSG on the level of MDA. We performed a comprehensive search of PubMed, the Institute for Scientific Information Web of Science, Embase, Scopus, and Cochrane Library for related contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…32 Therefore, MDA content is an important parameter reflecting the potential antioxidant capacity of cells, which can reflect the rate and intensity of lipid peroxidation of cells and indirectly reflect the degree of tissue peroxidation damage. 33 The results of this study showed that SA could decrease the SOD and GSH-px levels of HepG2 cells, while increasing the MDA levels, with statistical significance ( P < .05). The results showed that SA could induce oxidative damage and apoptosis of HepG2 cells, indicating these as one of the important ways of its anti-liver cancer activity.…”
Section: Discussionmentioning
confidence: 59%
“…32 Therefore, MDA content is an important parameter reflecting the potential antioxidant capacity of cells, which can reflect the rate and intensity of lipid peroxidation of cells and indirectly reflect the degree of tissue peroxidation damage. 33 The results of this study showed that SA could decrease the SOD and GSH-px levels of HepG2 cells, while increasing the MDA levels, with statistical significance ( P < .05). The results showed that SA could induce oxidative damage and apoptosis of HepG2 cells, indicating these as one of the important ways of its anti-liver cancer activity.…”
Section: Discussionmentioning
confidence: 59%
“…Oxidative stress in diabetic patients leads to more severe diabetic complications. Lipid peroxidation results from the interaction of the lipid bilayer of a cell membrane with ROS and oxygen derived free radicals, producing malondialdehyde (MDA) ( 95 , 96 ). Elevated levels of MDA lead in subjects with T2D to many physiological effects, such as influencing the structural integrity of the cell membrane, inactivating surface enzymes and receptors on the membrane, and causing errors in cell regulation ( 97 ).…”
Section: Introductionmentioning
confidence: 99%